Borderline Crossings in Sharon Pollock’s Out-Law Genres: Blood Relations and Doc - Kerr, Rosalind (Theatre Research in Canada / Recherches théâtrales au Canada, 1996)
Sharon Pollock’s well-known plays, Blood Relations and Doc, can be read as "out-law genres" by extending the criteria which Caren Kaplan has outlined to designate women’s renegade texts to theatrical representations. Both plays mix conventionally unmixable theatrical elements and use collaborative discursive practices to expose the myth that texts are individually authored, creating alternative texts based on a discourse of situation or a "politics of location." After her split-subject representation of the notorious parent-killer, Lizzie Borden, Pollock crosses back into Canadian territory to create her own version of the excluded daughter’s revenge in Doc where Catherine sets out to murder her father’s reputation symbolically. Taken together, Pollock’s plays, which rescue lost women’s stories, point to a new dramatic future capable of expressing revolutionary transnational feminisms. Les pièces bien connues de Sharon Pollack, Blood Relations et Doc, peuvent être interprétées comme des genres "hors la loi" en étendant les critères détaillés par Caren Kaplan pour désigner les textes renégats de femmes à des représentations théâtrales. Les deux pièces mélangent des éléments théâtraux traditionnellement polarisés et emploient des pratiques discursives collaboratives pour exposer le mythe qui veut que la paternité des textes soit singulière et non collective, créant ainsi des textes alternatifs basés sur un discours de situation ou sur une "politique d’emplacement". Suite à sa représentation de "sujet divisé" de la meurtrière notoire, Lizzie Borden, Pollock retourne au territoire canadien pour créer sa propre version de la vengeance de la fille exclue dans Doc où Catherine se met à tuer symboliquement la réputation de son père. Considérées ensemble, les pièces de Pollock, qui préservent des histoires de femmes perdues, signalent un nouvel avenir dramatique capable de l’expression des féminismes transnationals révolutionnaires.